Platform development for control of induction machine (Part II control algorithm verification) - Kang, Jia Yi (2015)
The uses of induction motor has been widely use throughout human history and in various application from generating of electricity to powering household appliances in our daily activities. Due to increasing application in sophiscated technology hence proper controlling of the speed of the induction motor is necessary and has led to increase emphasis and study on the various method in this area. In this report, the main focus will be on the discussion of the indirect flux oriented control of the induction motor which is a close loop sensorless speed control of the induction motor. In addition two different commonly used modulation technique, Space Vector Pulse width modulation (SVPWM) and Sinusoidal Pulse Width modulation(SPWM) will be employed in driving the motor and their difference will be investigated and compared. There will be hardware and software discussion, however the main emphasis will on the software discussion in this report. Matlab Simulink simulation and simulation results of the control algorithm will be discussed followed by introduction of the hardware component used in this project and finally an introduction of the microcontroller board used in the software and hard ware integration. Another method of controlling the speed of the motor is the Variable Voltage Variable frequency(VVVF) method, this method while simpler to implement, is an open loop system unlike the close loop system and hence does not have controller to regulate the output. In this project the VVVF method will be used in verifying whether the software control algorithm for VVVF and the hardware constructed could be successfully integrated and will act as a stepping stone for the future implementation of the close loop algorithm.